Biodiesel production from Neochloris oleoabundans by supercritical technology - Hegel, Pablo Ezequiel (2017)
Oleaginous microalgae have been proposed as a sustainable alternative biomass to produce biodiesel in order to substitute conventional vegetable oils derived from oilseed crops. Particularly, recent studies pointed out the potential of N. oleoabundans, cultured in seawater or in anaerobically digested dairy manure, to produce triglycerides with high content of monounsaturated fatty acids. The supercritical technology has been recognized as a green sustainable alternative to transform biomass into valuable products. Thus, the aim of the present wok was to study the direct supercritical alcohol processing of partially dried N. oleoabundans biomass and later reaction products fractionation by supercritical CO2 or liquid n-hexane. A direct alcoholysis of microalgae biomass was carried out at different temperatures (250 °C and 280 °C) and increasing reaction times in order to evaluate the fatty acid ester production. Bio-oils from microalgae with up to 35 wt.% fatty acid esters were obtained by two fold extraction with n-hexane. Conversely, supercritical CO2 fractionation produced upgraded bio-oils with up to 74 wt.% of fatty acid esters content.